Cardiovascular abnormalities and its correlation with genotypes of children with osteogenesis imperfecta - Zhao, Dichen; Liu, Yongtai; Liu, Jidong; Hu, Jing; Zhang, Qian; Wang, Ou; Jiang, Yan; Xia, Weibo; Xing, Xiaoping; Li, Mei (Frontiers in Endocrinology, 2022)
Objectives: Osteogenesis imperfecta (OI) is a rare disorder of abnormal production or modification of type I collagen, which is caused by mutations in COL1A1, COL1A2 or other genes. We investigate the cardiac abnormalities and its correlation with pathogenic mutations in children with OI. Methods: A cross-sectional comparative study was completed in a relatively large sample of OI children, who were matched with controls regarding body surface area (BSA). All echocardiography was performed by experienced cardiologists. Skeletal and extra-skeletal phenotypes of OI patients were evaluated. Pathogenic mutations of OI were detected by a next-generation sequencing panel and confirmed by Sanger sequencing. Results: A total of 69 OI children and 42 normal children matched in BSA were enrolled. Abnormalities of echocardiography were found in six OI children, including enlarged left atrium (n=5), increased internal diameter of the left ventricle (n=1), who all carried the COL1A1 mutation. Mild regurgitation of mitral or tricuspid valves was observed in 26 OI patients. Compared with healthy controls, OI children had significant larger values in the main pulmonary artery (MPA) (1.84 vs 1.60 cm, P < 0.01), left atrial diameter (2.58 vs 2.11 cm, P < 0.001), left ventricular internal dimension at end-diastolic (LVEDd) (3.85 vs 3.50 cm, P < 0.05) and lower left ventricular ejection fraction (LVEF) (68.40% vs 71.74%, P < 0.01). Moreover, OI patients with COL1A1 mutation tended to have greater MPA, larger diameters of left atrial and LVEDd, and lower LVEF than healthy controls. COL1A1 mutation had a significant correlation with dilated MPA ( = 1.557, P < 0.01), LAD (β = 3.915, P < 0.001), and LVEDd (β = 2.714, P < 0.01), and decreased LVEF (β = -3.249, P < 0.01). Conclusions: Cardiovascular alterations were identified in OI children, including increased dimensions of the main pulmonary artery and left chamber, and low left ventricular ejection fraction. The cardiovascular abnormalities seemed to be closely related with COL1A1 mutation and defects of type I collagen, which expanded our understandings of the cardiac phenotypes of OI children.